Intelligence technologies and low-carbon consumption behavior: evidence from Chinese app “Ant Forest” - Ding, Chaoxun; Ye, Jiawen; Wu, Xuepin; Zhang, Ruidan (Frontiers in Environmental Science, 2025)
Reducing carbon emissions is crucial for combating climate change, and low-carbon consumption is vital for carbon reduction. While intelligence technologies may reshape consumption, how they affect low-carbon consumption behavior and the underlying mechanisms are underexplored. Using the Attitude-Context-Behavior (ACB) theory, this study investigated whether intelligence technologies can promote low-carbon consumption, focusing on attitudinal factors’ mediating effect. With 399 Ant Forest users, models were constructed and regression analyses were carried out. The results showed that: (1) Attitudinal factors positively influence consumers’ low-carbon consumption behavior; (2) Contextual factors, including intelligence technologies, media campaigns, policy regulations, interpersonal influence, and spiritual incentives all positively affect low-carbon consumption behavior; (3) These contextual factors enhance low-carbon consumption behavior via attitudinal factors. To promote low-carbon consumption among Chinese residents, accelerating intelligence technology development, maintaining awareness campaigns, and enhancing self-efficacy are essential for a low-carbon societal shift.